Analisis Hubungan Shift Kerja dan Situasi Kerja dengan Kelelahan Kerja pada Security di PT XYZ Balikpapan - Lina Yuliana; Jordan Dearvin Krisda Kamma; Yan Fuadi (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2023)
fatigue is a problem that often occurs in the workplace, including security workers. Fatigue is a process that results in a decrease in welfare, capacity or performance as a result of work activities caused by several factors, namely work shifts and work situations will cause fatigue. This study aims to determine whether there is a relationship between work shifts and work situations with fatigue in security at PT XYZ Balikpapan. The research method used a quantitative research using a cross sectional study design. The research instrument used the Industrial Fatigue Research Committee (IFRC) questionnaire. The results of this study were 20 security who worked in a shift system who had low fatigue as many as 20 people (40%), who had moderate fatigue as many as 15 people (30%), who had heavy fatigue as many as 11 people (22%), while who had very severe fatigue as many as 4 people (8%). For comfortable work situations as many as 45 people (90%), less comfortable as many as 5 people (10%), very uncomfortable none. The results of the analysis using the Spearman Rho test obtained a p value = 0.000 where p <0.05 which means there is a relationship between work shifts and fatigue and work situations obtained p value = 0,018 where p <0.05 which means there is a relationship between work situations with fatigue.